Identification of De Novo Radio-Tartaglia Syndrome and Comparison of Clinical and Molecular Characteristics with Those of 1p36 Deletion Syndrome - Hyun-Young Kim; Jeehun Lee; Ja-Hyun Jang; Jong-Won Kim; Jiwon Lee; Mi-Ae Jang (Annals of Child Neurology)
Purpose Radio-Tartaglia syndrome (RTS; Mendelian Inheritance in Man [MIM]: 619312) is a rare neurodevelopmental disorder with few reported cases and limited research. It has recently been reported that the clinical features of RTS overlap with those of 1p36 deletion syndrome (1p36DS), a common chromosomal deletion characterized by clinical and molecular heterogeneity. This study aims to report on a Korean patient with RTS and compare the clinical and molecular features with those of patients with 1p36DS. Methods A 3-year-old boy was brought to the hospital and underwent whole genome sequencing to evaluate developmental delay and multiple anomalies. This led to the identification of a de novo truncating variant in SPEN. We retrospectively investigated cases of 1p36DS that were either newly diagnosed at our institution or previously reported in the literature and databases. Results The clinical profile of RTS includes developmental delay/intellectual disability, hypotonia, feeding difficulties, congenital heart defects, and facial dysmorphisms. SPEN is frequently found within the deleted region associated with 1p36DS. However, in all reported Korean cases of 1p36DS, the deletions were distal and did not involve SPEN; despite this, the clinical features of the disorder overlap considerably with those of RTS. Conclusion SPEN is a newly identified gene that plays a role in various developmental processes. Therefore, it is essential to include SPEN in genetic testing when diagnosing patients suspected of having a neurodevelopmental disorder. Additional research is required to explore the molecular and clinical features, as well as the prognosis, of patients with either an isolated SPEN mutation or one that co-occurs with 1p36DS.